Sticky expectations and consumption dynamics - Christopher D. Carroll; Edmund Crawley; Jiri Slacalek; Kiichi Tokuoka; Matthew N. White (European Central Bank (ECB), 2018)
Macroeconomic models often invoke consumption "habits" to explain the substantial persistence of macroeconomic consumption growth. But a large literature has found no evidence of habits in the microeconomic datasets that measure the behavior of individual households. We show that the apparent conflict can be explained by a model in which consumers have accurate knowledge of their personal circumstances but "sticky expectations" about the macroeconomy. In our model, the persistence of aggregate consumption growth reflects consumers' imperfect attention to aggregate shocks. Our proposed degree of (macro) inattention has negligible utility costs, because aggregate shocks constitute only a tiny proportion of the uncertainty that consumers face.
Keywords: D83; D84; E21; E32; 330; Consumption; Sticky Expectations; Habits; Inattention; Imperfect Information